Competências para análise crítica de questões da provinha Brasil: estudo de caso com docentes alfabetizadores de um município catarinense - Nazário, Fabiana Zulma Goulart (2010)
This dissertation has analyzed how ten literacy teachers from the south of Santa Catarina answer four proposed tasks about selected issues from the second stage of 2009 edition of “Provinha Brasil”. More specifically, the research has analyzed teacher’s skills to: a) answer the questions; b) identify axes of competences and descriptors of abilities tested in each one of the questions, and c) identify formulation processes of each one of the questions. Teachers have answered correctly 93.6% of the test, suggesting they have required linguistic skills to answer the proposed items. Teachers have answered intuitively the objects of the questions in 47.5% of the cases, and the reason for the inclusion of the issue in 28.2% of the cases. Axes of competences and descriptors of abilities are not mentioned in the answers, because teachers do not know the assumed terms of “Provinha Brasil”, which are based on Brazilian ProLiteracy Program. Teachers have answered correctly the methodology of formulating questions only in 10% of the cases, indicating little or no knowledge about crucial linguistic criteria to elaborate the questions. These findings emphasize the need of in-service training that considers: the internalization of a minimum set of theoretical elements of the proper linguistic terminology and the internalization of the matrix of competences assumed by the methodology of Brazilian Pro-Literacy Program, in general, and “Provinha Brasil”, in particular